5th European conference of the international federation for medical and biological engineering 14-18 September 2011, Budapest, Hungary - Jobbagy, Akos (IFMBE Proceedings, 2012)
This volume presents the 5th European Conference of the International Federation for Medical and Biological Engineering (EMBEC),  held in Budapest, 14-18 September, 2011. The scientific discussion on the conference and in this conference proceedings include the following issues: - Signal & Image Processing - ICT - Clinical Engineering and Applications - Biomechanics and Fluid Biomechanics - Biomaterials and Tissue Repair - Innovations and Nanotechnology - Modeling and Simulation - Education and Professional